New View To Problem Perimenopausal Osteoporosis - Zaripova Dilnoza Yashinovna (International Journal on Human-Computing Studies, 2024)
Worldwide, perimenopausal osteoporosis is one of the most common gynecological pathologies among women and numerous studies in recent years have focused on the prevention of this pathology to identify high-risk groups of burden. To date, one of the serious problems requiring immediate treatment is to determine the role of the relationship of biochemical markers with steroid hormones among women in the perimenopausal period older than 50 years, which would allow treating patients burdened with this disease by in-depth analysis of metabolic and hormonal disorders in the blood.